Bioactivity of some medicinal plant extracts against Musca domestica L. - Vijigiri1, P.P. Sharma1*, A.B. Pardeshi2; Dinesh (Journal of Ecobiotechnology, 2011)
Musca domestica, is a major vector responsible for spreading many human and veterinary pathogenic organisms. Many methods have been tried to control them but none is found to be 100% effective and even some synthetic ones have given good results but their residues which are being accumulated in water, food, milk, etc. have become serious cause of concern. These residues are known to remain active for many years and their degradation is slow. Moreover, chemical pesticides and insecticides show good results in the beginning but later on these become less effective due to the resistance generated by the insects / pests. Therefore, there is every need to find out alternative for the chemical pesticides. By topical application of some ethnolic extracts the percentage mortality were recorded. Percent mortality and index of repellency induced by the extracts found to be dose-dependent. Extracts of the two plant species may be useful as insecticides for controlling the houseflies and should be exploited as a component of integrated vector control strategies or could be useful in the search of new insecticidal natural compounds. In the present study the different concentrations extracts of some plants were tested for adulticidal and repellent activity against Musca domestica L. The percentage mortality was found to increase with higher concentrations of plant extracts which indicates direct relationship between the dose and percent mortality. The plant Artemisia nilgirica (C.B.Cl.) Pamp. and Annona squamosa L. were shown wide spectrum activity to control Musca domestica L. While some other species such as Blumea eriantha DC., Calotropis procera (Ait.) R. Br., Lavandula bipinnata O. Ktze. have also shown the activity.